"Laudate Deum": A Reminder of the Planet’s Solidarity Sustainability - Roca Alcázar SJ, Fernando (2026)
Laudate Deum highlights the relevance of Laudato si’ and the urgency of moving forward more quickly and effectively to avoid reaching tipping points and points of no return that will endanger the planet's stability, affecting the most vulnerable people even more.